Geothermal resource management - a reservoir simulation approach - the Paris Basin case - Papachristou, M.; Ungemach, P.; Fytikas, M. (Bulletin of the Geological Society of Greece, 2013)
Numerical modeling has become an indispensable part of geothermal resource management, especially when long-term production is involved, offering the ability to forecast the reservoir behavior under various exploitation scenarios. This paper illustrates the simulation results of the “Dogger” reservoir in Val de Marne region (south of Paris), where 16 doublets (production-injection wells) are still in operation today. The “Dogger” low enthalpy geothermal reservoir in Paris Basin is being under intensive and systematic exploitation since the early 1980’s. Almost 40 years after the initiation of the heat mining project, the longevity of the reservoir and applications have become critical issues for achieving the exploitation system’s sustainability. The simulation covers a period of 52 years (1984-2035), attempting to recreate the exploitation history and to provide an early estimation of the time-space variation of pressure and temperature inside the reservoir under future production/injection schemes and schedules. For the majority of the wells, the calculated production temperatures match quite well the field data up to the year 2011. The prediction models indicate that certain modifications in the development scheme could result in the stabilization of the fluids temperature, or at least in slower depletion rates.